Prevalence of Burnout among National Guard Health Affairs Physicians in Dammam, Saudi Arabia - A Cross- sectional Study - Wajid, Syed (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: This study aimed to determine the prevalence of burnout among physicians of National Guard Health Affairs, Dammam Saudi Arabia. Methods: A cross-sectional, descriptive study among physician working in the National Guard Health Affairs was conducted in 2016. The Oldenburg Burnout Inventory questionnaire was used. A total of 140 medical doctors invited for the study. A test of ANOVA was performed to find any difference between the variables and a P < 0.05 represents a statistically significant difference. Results: The overall response rate was 65.51%. The mean age standard deviation of respondents was 40 (9.39) years; years of experience 14.03 Â± 8.81, and the mean working hours per week 14.03 Â± 8.81; of the respondent, 62.1% were male, 37.9% were female, 36.8% of Saudi nationalities, while 63.2% were non-Saudi. There was no significant difference found in prevalence of burning, among different health specialties, gender, and nationalities with a value of P = 0.952, P = 0.806, and P = 0.055, respectively. Conclusion: The sttudy findings revealed that prevalence of burnout among physicians was found to be moderately high and is more common among medical profession. It is recommended that awareness of the problem should be underlined; programs need to be put in place to reduce the prevalence of burnout syndrome.